Shifting taxes from labor to consumption: More employment and more inequality - Nico Pestel; Eric Sommer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This paper investigates the effect of shifting taxes from labor income to consumption on labor supply and the distribution of income in Germany. We simulate stepwise increases in the value-added tax (VAT) rate, which are compensated by revenue-neutral reductions in income-related taxes. We differentiate between the personal income tax (PIT) and social security contributions (SSC). Based on a dual data base and a microsimulation model of household labor supply behavior, we find a regressive impact of such a tax shift in the short run. When accounting for labor supply adjustments, the adverse distributional impact persists for PIT reductions, while the overall effects on inequality and progressivity become lower when payroll taxes are reduced. This is partly due to increases in aggregate labor supply, resulting from higher work incentives.
urn:nbn:de:bsz:180-madoc-394727
Keywords: C63; D31; H23; 330; income and payroll taxes; consumption taxes; microsimulation; inequality; Germany